MEMAHAMI WELTANSCHAUUNG AL-QUR’AN PERSPEKTIF PENDEKATAN KONTEMPORER - Muhammad Yusuf (Tanzil: Jurnal Studi Al-Quran, 2015)
The classical reading methods which are literal textual as an intellectual response from Muslims scholars to socialcultural dynamic which related to their life at that time. The urgency to understand the Qur’an in a holistic manner was needed in addressing the problems of life, in addition to the development of the qur’anic study necessitates the alignment between scientific research, interpretation of the Qur’an, universal benefit and the value of wisdom in the same breath with weltanschauung of al-Qur’an. Implementation of such commentary tradition in the context of local wisdom is not intended to limit the meaning of the Qur’an text, but rather on the dialectic between interpretation, cultural and readers that can not be separated. This article tries to convey Bugis-Makassar cultural values as an example of how to implement the relevant moral ideas in accordance with the teachings of the Qur’an.